FBI : The Edge - Book 4 - Coulter, Catherine (New York : G.P. Putnams Sons, 1999)
FBI agent Ford "Mac" MacDougal becomes caught in a mysterious web of evil when he rushes to the small town known as The Edge to be with his sister who is in a coma after driving her car off a cliff, only to have her wake up and then disappear.
Keywords: Missing persons -- Oregon; Fiction; Brothers and sisters -- Oregon; Fiction; Oregon -- Fiction; Oregon -- Fiction; Thriller